2012
DOI: 10.1111/j.1753-318x.2011.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Application and validation of mortality functions to assess the consequences of flooding to people

Abstract: The assessment of potential consequences of a flood event to the exposed population is a key question for flood risk managers. This issue is increasingly a triggering research on assessing potential numbers of fatalities because of flooding. In the past, mortality functions were proposed to estimate the fatalities in areas that are exposed to a hazard because of flood defence failures‐in the Netherlands. This paper describes a study undertaken to validate those mortality functions and assesses their applicabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Jonkman et al (2008) provides a thorough and comprehensive review of these methods as well as describing a new approach. This approach has been further verified by Di Mauro and de Bruijn (2012). Relatively recently, Agent, or Individual, based models have been increasingly developed and applied to support emergency planning and evacuation modelling in relation to floods, BC Hydro (2004), Dawson et al (2011) and, for example.…”
Section: Life Lossmentioning
confidence: 84%
“…Jonkman et al (2008) provides a thorough and comprehensive review of these methods as well as describing a new approach. This approach has been further verified by Di Mauro and de Bruijn (2012). Relatively recently, Agent, or Individual, based models have been increasingly developed and applied to support emergency planning and evacuation modelling in relation to floods, BC Hydro (2004), Dawson et al (2011) and, for example.…”
Section: Life Lossmentioning
confidence: 84%
“…Three factors refer to flood characteristics. Di Mauro and De Brujn [36] stated that results are largely influenced by the extent of the flooded area, which then raises questions about the simulation of flood hazards. The introduction of a new parameter based on vulnerability may considerably enhance fatality estimation.…”
Section: Limits Of Fatality Assessmentsmentioning
confidence: 99%
“…There is a need to have systematic techniques that can predict flood based on those causes which can avoid from any catastrophic disaster to human population [5][6]. Recent research had shown that data mining techniques had gained its popularity and had been used in predicting flood [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%